The effect of flaxseed intake on appetite reduction: A systematic review of randomized clinical trials. (2nd August 2022) - Zarei, Mahtab; Adeli, Shaghayegh; Hosseini, Shabnam; Daneshzad, Elnaz
Abstract: Appetite control has attracted many scientists' attention recently since it can lead to weight management and the prevention of further metabolic disorders. Many studies have been carried out to assess the effect of flaxseed on satiety perception but the results are controversial. This study aims to review these results comprehensively. PubMed/Medline, Web of Science, Scopus, and Cochrane databases were searched for related papers on June 2021. The searched keywords for appetite were: visual analog scale, appetite, desire to eat, satiation, satiety, hunger, fullness, and for Flaxseed they were: flax, flax*, linseed*, lignin*, Linseed Oil, flaxseed, ground flaxseed, flaxseed oil, and Linum usitatissimum. The 13 included studies were inconsistent in results and some of them found no significant effect of flaxseed on the considered outcomes. However, three studies revealed a significant reduction in hunger perception as well as appetite. Moreover, two studies found a decreasing effect on prospective consumption. Three studies observed a positive significant effect on fullness and satiety. Although there are a limited number of documents related to the effect of flaxseed on appetite perception, or its equivalent terms, the available studies suggest the potential role of flaxseed in decreasing appetite and hunger.